Enhanced thermoelectric performance in Sb–Br codoped Bi2Se3 with complex electronic structure and chemical bond softening. Issue 3 (11th January 2022) - Zhang, Ju; Zhong, Shiqi; Ke, San-Huang
Abstract : A detailed description of the charge density difference of BiSb(Se0.92 Br0.08 )3 . Abstract : Prior experimental work showed that Bi2 Se3, as a sister compound of the best room-temperature thermoelectric material Bi2 Te3, has remarkably improved thermoelectric performance by Sb–Br codoping. But the relationship between its crystalline structure and thermoelectric properties is still unclear to date. Here, we use first-principles calculations to explore the possible reasons for such improvement. The electronic structures of Bi2− x Sb x (Se1− y Br y )3 ( x = 0, 1, 2; y = 0, 0.08) are systematically investigated. Significant effects of 8% Br codoping in BiSbSe3 are found. First, the Br atom acts as an electron donor, thus greatly increasing the carrier concentration. Second, similar to the effect of Sb doping, Br codoping further improves greatly the degeneracy of the conduction band edge, which leads to a remarkably increased density-of-states effective mass without deterioration of the carrier mobility, and simultaneously preserves a large Seebeck coefficient of ∼−254 μV K −1 at 800 K. In addition, the Br codoping softens the chemical bonds, which enhances anharmonic scattering and further reduces the lattice thermal conductivity. We predict that the maximum zT of BiSb(Se0.92 Br0.08 )3 at 800 K can reach 0.96 with the carrier concentration of 9.22 × 10 19 cm −3 . This study rationalizes a potential strategy to improve the thermoelectric performance of Bi2 Se3 -based thermoelectric materials.